Análise da diversidade cariotípica de Characidae da bacia do São Fracisco - Peres, Wellington Adriano Moreira (Universidade Federal de São Carlos, 2005)
Family Characidae consists of approximately 30 highly diversified subfamilies that probably do not comprise a monophyletic group. However, a few particular subfamilies may constitute monophyletic groups sharing specializations. In the present work, nine specimens belonging to six genera were analyzed using classic staining techniques as well as fluorescent in situ hybridization (FISH) and GCspecific fluorochromes, such as Chromomycin A3 (CMA3). A diploid number of 2n=58 chromosomes was observed in Myleus micans, with 26M+18SM+8ST+6A; 2n=50 in Astyanax lacustris with 8M+20SM+16ST+6A; 2n=50 in A. altiparanae with 8M+20SM+12ST+10A; 2n=50 in Astyanax scabripinnis with 12M+24SM+2ST+6A; 2n=50 in Orthospinus franciscensis with 12M+30SM+2ST+6A; 2n=52 in Piabina argentea with 8M+14SM+16ST+14A; 2n=52 and three cytotypes in Serrapinnus heterodon, with 17M+20SM+14ST+1A, 16M+20SM+14ST+2A and 15M+20SM+14ST+3A; 2n= 52 in Serrapinnus piaba with 16M+20SM+14ST+2A; and 2N=50 in Hasemania nana with 8M+42SM. FISH results with the 18S rDNA probe indicated the presence of these genes in the chromosomes where NORs were active, besides additional sites, as seen in M. micans, A. scabripinnis, P. argentea and S.piaba. Similar to the NOR sites, the 5S rDNA regions were evidenced in different numbers and positions throughout the studied species. The data obtained corroborate the chromosome diversity often reported for Characidae, reinforcing its polyphyletic condition.
Keywords: Citogenética; Characideo; Fish - DNAr 18S; DNAr 5S; Evolução cariotípica; CIENCIAS BIOLOGICAS::GENETICA